Social Pathology in Susan Arisanti’s Novels and Their Relevances with Social Reality - Dede Indra Wahyu Nugroho; Agus Nuryatin; Nas Haryati Setyaningsih (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The novels by Susan Arisanti were chosen as research object because the stories presented are interesting which tell about the social conditions of society and in the novels, there are allegations of the existence of social pathologogy phenomena. The aim of the research is to analyze forms, causal factors and impacts of social pathology in Susan Arisanti’s novels and to analyze the relevance of social pathology in Susan Arisanti’s novels with social reality. The design of this research is qualitative research with a literary sociology approach. The Research data is in the form of text fragments which are suspected to containing forms, causal factors and impacts of social pathology. The data source for this research is novels by Susan Arisanti. The results of this research found forms of social pathology in Susan Arisanti’s novels including (1) crime/criminality; (2) prostitution; (3) gambling; (4) corruption; (5) mental confusion; (6) jevenile delinquency. The factors that cause social pathology found are (1) internal factors and external factors; (2) obsession and bad family conditions; (3) situational factors; (4) needed; (5) the wrong way of maturing the mind so that a feeling of betrayal arises; (6) lack of self-control, negative disposition, and lack of supervision. The impact of social pathology that were found are (1) conflicts, material losses, loss of mutual trust, legal proceedungs, non-mateial losses; (2) the dertruction of the foundations of family life; (3) unstable economic conditions and distubed mental health; (4) impact of corupption is imprisonment and unprofessional work; (5) hurt feelings; (6) growing into a bad person, being rebellious, and feeling osctracized by the environment.This research has ralevance with social reality with reference to the author’s residence in Lampung Province and more broadly in Indonesia and the news of social pathology before the novels was published.